2022
DOI: 10.3389/fnbeh.2022.1040719
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS neuroimaging in olfactory research: A systematic literature review

Abstract: There are a number of key features which make olfaction difficult to study; subjective processes of odor detection, discrimination and identification, and individualistic odor hedonic perception and associated odor memories. In this systematic review we explore the role functional near-infrared spectroscopy (fNIRS) has played in understanding olfactory perception in humans. fNIRS is an optical neuroimaging technique able to measure changes in brain hemodynamics and oxygenation related to neural electrical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Whilst the peak of activity may be beyond the depth of fNIRS monitoring abilities, task-based changes in regional cerebral blood flow may occur across a larger area within the cited region which may be detectable with fNIRS within the superficial aspects of these cortical regions. As summarised in Gunasekara et al (2022) , have used fNIRS to monitor the OFC during olfactory stimulation. Twelve of these studies reported fNIRS signal changes within the interrogated regions of the OFC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the peak of activity may be beyond the depth of fNIRS monitoring abilities, task-based changes in regional cerebral blood flow may occur across a larger area within the cited region which may be detectable with fNIRS within the superficial aspects of these cortical regions. As summarised in Gunasekara et al (2022) , have used fNIRS to monitor the OFC during olfactory stimulation. Twelve of these studies reported fNIRS signal changes within the interrogated regions of the OFC.…”
Section: Discussionmentioning
confidence: 99%
“…Using a well-established task which is known to involve olfactory processing, olfaction can be studied using fNIRS, with regions of interest accessible in the frontal and parietal lobes. As summarised in Gunasekara et al (2022) , multiple studies have already used fNIRS to study olfaction. These studies predominantly considered prefrontal regions of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation